2019
DOI: 10.1177/0300060519860329
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the cytotoxic T lymphocyte-associated protein-4 immune regulatory gene and their impact on inhibitor development in patients with hemophilia A

Abstract: ObjectiveThe development of inhibitors against infused factor VIII represents the most severe complication of substitution therapy in hemophilia A (HA) patients. Data on risk factors for inhibitor formation in Iraqi Kurdish patients with HA are unavailable. This study aimed to evaluate the impact of two single nucleotide polymorphisms (SNPs) in an immune regulatory gene in the emergence of inhibitors.MethodsWe focused on 126 patients with either severe or mild/moderate HA presenting with and without inhibitors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…We found that CTLA4-expression was inversely related to the presence of inhibitors and positively correlated with the induction of tolerance, underscoring earlier research in which polymorphisms in the CTLA4 gene were associated with the risk of inhibitor development. 54 57 Moreover, a hemophilic mouse model also showed a beneficial role of CTLA4 in ITI. 58 In this study, injection of CTLA4-immunoglobulin (CTLA4-Ig) prevented the primary (inhibitor) antibody response to FVIII.…”
Section: Discussionmentioning
confidence: 99%
“…We found that CTLA4-expression was inversely related to the presence of inhibitors and positively correlated with the induction of tolerance, underscoring earlier research in which polymorphisms in the CTLA4 gene were associated with the risk of inhibitor development. 54 57 Moreover, a hemophilic mouse model also showed a beneficial role of CTLA4 in ITI. 58 In this study, injection of CTLA4-immunoglobulin (CTLA4-Ig) prevented the primary (inhibitor) antibody response to FVIII.…”
Section: Discussionmentioning
confidence: 99%
“…The CTLA-4 rs5742909 polymorphism ( C > T ) is in the promoter region of exon 1 of the CTLA-4 gene, affecting the ATG transcription initiation codon [ 54 ]. This SNP could alter the transcription factor binding site [ 22 , 55 , 56 , 57 ]. In addition, the CTLA-4 rs5742909-T allele has been linked to increased RNAm expression and higher levels of the CTLA-4 protein [ 53 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…In autoimmune diseases, polymorphisms in the immune response genes were reported to be related to the formation of antibody. In addition, SNPs in the regulatory regions of cytokine genes are crucial components in the pathogenesis of various diseases, including HA [21,22]. Individual immune response traits might in uence a patient's reaction to exogenous factor VIII.…”
Section: Discussionmentioning
confidence: 99%